Marxism and the Philosophy of Language / V. N. Volosinov - Matejka Ladislav; Titunik I. R (Harvard University Press, 1986)
In this book a reader can discover the ideas of Bakhtin and his circle about language, not as a conceptual metaphor, but as that aspect of human life which is in fact the subject matter of a cumulative science. The Philosophy of Language and its significance for Marxism, The Study of Ideologies and Philosophy of Language, Concerning the Relation of the Basis and Superstructures, Philosophy of Language and Objective Psychology, Toward a Marxist Philosophy of Language, Two Trends of Thought in Philosophy of Language, Language and Speech and Utterance, Verbal Interaction, Theme and Meaning in Language, Toward a History of Forms of Utterance in Language Constructions (Study in the Application of the Sociological Method to Problems of Syntax), Theory of Utterance and the Problems of Syntax, Exposition of the Problem of Reported Speech, Indirect Discourse and Direct Discourse and their Modifications, Quasi-Direct Discourse in French and German and Russian, Appendices, Index.